Ministry of Education: Guidelines for the Lower Secondary School Proficiency Examination (LSPE) - Trinidad and Tobago. Ministry of Education (Ministry of Education, Trinidad and Tobago, 2023)
The Lower Secondary School Proficiency Examination (LSPE) is intended to replace the Primary School Leaving Certificate Examination (PSLCE) from the year 2024 and onwards. It is designed to provide students with a form of certification in key competencies such as Mathematics, English Language, English Comprehension and Composition and General Studies. Whereas the first administration targets Form 2 students at the secondary level for academic year 2023/24 who scored less than 50% at SEA 2022, the LSPE will be opened to all institutions/students who previously sat the PSLCE, inclusive of: SERVOL Life Centre, adult education centre, correctional centre or facility, and other ministries. The LSPE draws its content from the Upper Primary School Curriculum (Standards 4/5) and the Lower Secondary NCSE (Forms 1 and 2). For students at the Secondary School level, the LSPE certificate will provide a pathway for students as they progress to the upper secondary school level. The assessment will be administered in June of each year with registration taking place in November/December of the previous year and dissemination of results by September of the year of administration. The items in the LSPE will comprise a mixture of open ended or constructed response (CR) and Multiple Choice Question (MCQ). The grading scheme will provide the following results: distinction, credit, pass and fail.
Keywords: Lower Secondary Proficiency; Examinations